Estudio de la percepción de la calidad en los usuarios del servicio de medicina general del Centro de Salud Tipo A de la Parroquia Lauro Guerrero, año 2023 - Lima Izquierdo, María Celeste (2024)
The research work was carried out at the Health Center Type A Lauro Guerrero, Paltas Canton. The general objective of the research was to assess the perception of quality among users of the general medicine service and the specific objectives were to describe the current situation of the service, measure the perception of quality among users and develop a proposal for improvement to strengthen user care activities. The methodology was based on a study with a mixed approach and an exploratory-descriptive scope, from a non-experimental action- research design. In addition, the SWOT tool, interview and observation sheet were used to determine the current situation and develop strategies for continuous improvement. In order to effectively and efficiently obtain the users' perception of quality, the SERVPERF model was applied, which consists of five dimensions: tangible elements, reliability, responsiveness, security and empathy; the Likert scale was used to give weight and importance to each of these dimensions, with a range from 1 to 5. The data collection tool used was an attitudinal questionnaire, comprising 22 statements, which was applied to 174 users of the general medicine service. The main results revealed that the dimension that generated the greatest impact on users was that of tangible elements, with an average of 3.57, while the responsiveness dimension obtained a less favorable impact, with an average of 2.73. The final result indicated that the overall perception of the quality of service was 3.21, which indicates that the users surveyed agree with the quality of the service provided. Finally, strategies were designed to improve the service quality of the unit under study.